Autonomy-supportive Political Climate and Attitudes to the Political System in Russia: How Does Self-Determination Theory Help in Understanding Political Attitudes - O.A. Gulevich; D.N. Chernov (Социальная психология и общество)
Objective. In this study, we analyzed the relationship between political efficacy (autonomy-supportive political climate) and attitudes to the political system in Russia. Background. Self-determination theory posits that individuals express more positive attitudes toward those who create an autonomy-supportive climate than toward those who create a controlling climate. Some studies conducted in democratic political regimes have shown that political efficacy, as an indicator of perceived autonomous climate, is positively associated with attitudes towards the political system. However, the question arises: to what extent does the positive relationship between political efficacy and attitudes toward the political system persist in countries with authoritarian political systems, as well as among individuals with different socio-demographic and psychological characteristics? Study design. Respondents participated in an online survey conducted on the YandexToloka platform (samples 1, 3, 5) and on social media platforms (samples 2, 4, 6). The study involved six samples: the first and second samples were collected in May-June; the third and fourth samples were collected in August-September; the fifth and sixth samples were collected in November-December 2022. Participants. 16656 Russian citizens took part in this study (N1 = 2767, N2 = 2580, N3 = 3193, N4 = 2482, N5 = 3234, N6 = 2400). The data was collected in the spring-autumn of 2022. Measurements. Participants completed questionnaires that measure personal and collective political efficacy (perceived autonomy-supportive political climate), cognitive and emotional attitude towards the political system, as well as a range of psychological (political interest, internal political efficacy, psychological well-being, generalized trust, national identification) and socio-demographic (gender, age, education, income) control variables. Results. The study reveals that both personal political efficacy and collective political efficacy (perceived autonomy-supportive political climate) were positively associated with political trust and system justification. Results from YandexToloka demonstrate that the link between personal political efficacy and attitudes towards the political system is stronger among individuals who are more interested in politics and consider themselves more informed in this area. The association between collective political efficacy and attitudes towards the political system is stronger among individuals with higher psychological well-being and stronger national identification. However, in all samples, it is found that the positive link between political efficacy and attitudes towards the political system holds after controlling for psychological and socio-demographic variables. Conclusions. The perceived autonomy-supportive political climate is an important factor in predicting Russians' cognitive and emotional attitude towards the political system. It plays a significant role for people belonging to different socio-demographic groups and possessing various psychological characteristics. People with an active political life, with high psychological well-being and national identification value it the most. The fostering of the autonomy-supportive political climate, which allows people to voice their opinions on social problems and influence political decisions, improves their attitudes towards the political system including federal political institutions.